Piperine Attenuates TBI-Induced Seizures via Inhibiting Cytokine-Activated Reactive Astrogliosis - Song, Yabei; Cao, Caiyun; Xu, Qiuyue; Gu, Simeng; Wang, Fushun; Huang, Xi; Xu, Shijun; Wu, Erxi; Huang, Jason H. (Frontiers in Neurology, 2020)
Peppers have been used in clinics for a long time and its major component, piperine (PPR), has been proven to be effective in the treatment of seizures. The purpose of this study was to investigate the effects of piperine on early seizures in mice after a traumatic brain injury (TBI) and to explore the mechanism of the drug against the development on TBI. Specific-pathogen-free-grade mice were randomly divided into six dietary groups for a week: control group, TBI group, three piperine groups (low PPR group with 10 mg/kg PPR, medium PPR group with 20 mg/kg PPR, and high PPR group with 40 mg/kg PPR), and a positive control group (200 mg/kg valproate). Except for the control group, all the other groups used Feeney free weight falling method to establish the TBI of closed brain injury in mice, and the corresponding drugs were continuously injected intraperitoneally for 7 days after the brain injury. The results from behavior and electroencephalogram showed that piperine attenuated the subthreshold dose of pentylenetetrazole-induced seizures compared with the TBI group. The western blot results showed that the expression levels of inflammatory factors tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) were reduced by piperine. The immunostaining results showed that the brain-derived neurotrophic factor (BDNF) was also reduced by piperine. In addition, positive cell counts of astrocytic fibrillary acidic protein (GFAP) in immuno-fluorescence showed that they were also reduced. Our data show that piperine treatment can reduce the degree of cerebral edema, down-regulate TNF-α, IL-1β, and BDNF, decrease the reactivity of GFAP in the hippocampus, and inhibit TBI-induced seizures.